The Myth Saint Thomás american and the cultural evidence in colonial America (Revista de História Regional, 2008)
This article presents some cultural evidences ocurred in the situations of contact between Europeans and indians in colonial america (sec. XVI and XVII). Showing the aboriginal myths resignification who assumed apostle Thomas identity to the christian missionaries.With this incorporation the jesuits earned while successive apostolic and indians were enclosed in the christian world.